2014
DOI: 10.1007/s12010-013-0699-8
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Development and Evaluation of Genetic Stability of Cryopreserved Dendrobium Hybrid Mature Seeds

Abstract: Vitrification, a simple, fast, and recommended cryopreservation method for orchid germplasm conservation, was evaluated for Dendrobium hybrid "Dong Yai" mature seeds. The genetic stability of regenerated seedlings was also evaluated using flow cytometry. Mature seeds from this hybrid were submitted to plant vitrification solution (PVS2) for 0, 0.5, 1, 2, 3, 4, 5, or 6 h at 0 °C. Subsequently, they were plunged into liquid nitrogen (LN) at -196 °C for 1 h and recovered in half-strength Murashige and Skoog cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…By determining the best dehydration time of explants at 0 °C, the toxicity of the vitrification solution can be reduced and, consequently, the exposure time to PVS2 solution can be increased for a successful cryopreservation protocol (Johari et al 2009, Vendrame et al 2008. Vendrame et al (2008) showed that pre-cooling treatment (ice) combined with PVS2 treatment for a period of time between 1 and 3 h was essential to allow proper germination of cryopreserved seeds of four commercial Dendrobium hybrids genotypes (Galdiano et al 2014). Likewise, in this study, the dehydration period was similar and 1 h in PVS2 can be recommended.…”
Section: IImentioning
confidence: 64%
“…By determining the best dehydration time of explants at 0 °C, the toxicity of the vitrification solution can be reduced and, consequently, the exposure time to PVS2 solution can be increased for a successful cryopreservation protocol (Johari et al 2009, Vendrame et al 2008. Vendrame et al (2008) showed that pre-cooling treatment (ice) combined with PVS2 treatment for a period of time between 1 and 3 h was essential to allow proper germination of cryopreserved seeds of four commercial Dendrobium hybrids genotypes (Galdiano et al 2014). Likewise, in this study, the dehydration period was similar and 1 h in PVS2 can be recommended.…”
Section: IImentioning
confidence: 64%
“…For example, mature seeds of Oncidium flexuosum (11% WC) and a Dendrobium hybrid (13% WC) were unable to germinate or exhibited a low germination percentage after direct immersion in LN [28,29]. The seeds of these species should be cryopreserved through a vitrification method combined with rapid cooling and rewarming [28][29][30].…”
Section: Vitrification Methodsmentioning
confidence: 99%
“…Freshly collected mature seeds were cleaned and dried over LiCl for 2 weeks and stored at 4 °C until used for the study (approximately 1 year). Lithium chloride-mediated drying is a commonly used method (Galdiano et al 2014 ). A pinch of seeds (ranging from 300 to 2000 seeds depending on the species) were transferred to hardened filter paper (Whatman, UK) and stapled.…”
Section: Plant Speciesmentioning
confidence: 99%
“…Seed and protocorm cryopreservation utilises a range of different available methods including: direct freezing, encapsulation-vitrification and droplet-freezing, each tested in several taxa (Sakai and Engelmann 2007 ; Sopalun et al 2010 ; Jitsopakul et al 2012 ; Hu et al 2013 ; Galdiano et al 2014 ; Teixeira da Silva et al 2014 ; Popova et al 2016 ). However, protocorms, a widely used propagule for cryopreservation, are prone to cryopreservation injury due to their cellular structure and high-water content.…”
Section: Introductionmentioning
confidence: 99%